STRATEGIC PLANNING AT PT AETRA AIR JAKARTA IN DRINKING WATER MANAGEMENT. - Zulfa Hananiawati (Program Studi Pendidikan Kependudukan dan Lingkungan Hidup, 2017)
The aim of this research is to determine how the strategy planning and the implementation in drinking water management by PT Aetra to deal with the universal access and based on Permen PU no. 18/PRT/M/2007. Analysis used descriptive qualitative with comparative approach between strategic planning and theory of strategic planning and management. As a commitment in the drinking water service excellence, strategic planning and management set out in the annual work meeting and resulted in business strategies implemented next year. Strategy planning which is formulated in the policies and regulations form in order to achieve the vision, mission and values. Strategic planning has not been considered environmental factors such as seasonal changes which are very influential in the water management of drinking water. The total of the precipitation influence in water management by Aetra especially in the quality of raw water instead of the quantity of raw water. In managing water, the concept of sustainable development has been applied and continues to be improving needed for a balance between profit, environmental and social.